PENENTUAN BLACK SPOT PADA RUAS JALAN DENGAN METODE UPPER CONTROL LIMIT (UCL) DI KOTA MATARAM - ROHANI ROHANI; HASYIM HASYIM (GANEC SWARA, 2024)
Traffic accidents in Mataram City increase every year. Over the last 4 years, Mataram City Police data shows that traffic accidents, one of the transportation problems, have increased quite significantly. To overcome this transportation problem, efforts are needed to reduce/minimize the number of accidents and one way that can be done is by determining areas prone to traffic accidents (black spots) in Mataram City so that transportation safety can be improved. Data from the Mataram City Police in the form of accident data is needed to determine areas prone to traffic accidents (Black spot). Next, the data was analyzed using the Accident Equivalent Number (AEK) parameters and the Upper Control Limit (UCL) method so that black spots could be arranged in Mataram City. The analysis results show that the accident-prone sections (black spots) in Mataram City are the Jln. Sriwijaya, Jalan Pejanggik, Jalan Sandubaya, Jln. Dr. Sudjono, Jalan Adi Sucipto, Jln. Catur Warga, and Jln. Ahmad Yani. Based on the type of accident, the highest was single hit (74%) and front-side crash (73%), the weather when the accident occurred was highest in sunny conditions (98%) at night, and the most people who had accidents were men. amounting to 74%, while the age range of 16-30 years is most often involved in accidents.